Determination of bed sediment load for rivers / Junaidah Ariffin and Wardah Tahir - Ariffin, Junaidah; Tahir, Wardah (2001)
Bed sediment load is essential in calculating the transport rate of sediments in rivers and several empirical equations have been developed using experimental and field data by past investigators. However it should be noted that the equations developed were based on controlled conditions done in the laboratory and sediments were of uniform sizes. Even if the empirical equation derived is based on field data, this does not seemed to match with our local conditions. The predicted rate of transport of bed sediments using these equations do not agree with the observed values. In view of this, several field data have been collected from river gauging stations in Selangor namely Kg. Lui Station for Sg. Lui, Kajang and Dengkil Station along Sg. Langat and Kg. Rinching Station along Sg. Semenyih to establish a relationship for the transport of bed load. The number of bed load samples taken at each cross-section in every observation vary between two to nine. The methods employed in the river gauging operation and sediment measurements depend largely on the flow conditions. In this research work the effective grain size of sediments was found from the S-curves. From the sieve analysis tests it was found that the river beds under study composed of more than 60 % of sand which has size ranges from 0.063 micron to 2 mm. A rating curve of discharge versus bed load has been prepared. A relationship for bed load transport have been established for rivers in Selangor.